The Effect of Relationship Marketing Components through Customer Gratitude on Customer Behavioral Loyalty in Retail Market - Amir Hossein Hejazian and Fereshteh Lotfizadeh, Seyed (British Journal of Marketing Studies, 2017)
Relationship marketing is seeking to establish relationships with target customers to shopping again from it in the future and encourage others to do so. Crating the great satisfaction in customers and focus on what they are worth to be considered, are  the best approach to keep  (retain ) customers and as a result their loyalty to the company will be stronger. The study population were supermarket customers in Zanjan city and 384 samples were selected according to Cochran formula. Data collection was carried out using a questionnaire and through simple random sampling. In this study, Cronbach's alpha with the amount of 76/0 was used to assess. And also, descriptive and inferential statistics were used to analyze the data and all statistical analyzes were performed using SPSS software. The results of this study showed that which of the component of relationship marketing through customer gratitude had a significant impact on Customer Behavioral loyalty.